Ameliorative Effect of Melatonin Against Reproductive Toxicity of Tramadol in Rats via the Regulation of Oxidative Stress, Mitochondrial Dysfunction, and Apoptosis-related Gene Expression Signaling Pathway - Motahareh Koohsari; Nematollah Ahangar; Ebrahim Mohammadi; Fatemeh Shaki (Addiction and Health, 2020)
Background: The aim of the present study was to investigate the protective properties of melatonin (MT)against oxidative stress, mitochondrial dysfunction, and apoptosis induced by tramadol-reproductive toxicityin male rats.Methods: The rats were divided into the 7 groups of control, melatonin (1.5 mg/kg), tramadol (50 mg/kg), andmelatonin (1, 1.5 and 2.5 mg/kg) administered 30 minutes before tramadol and vitamin C group (100 mg/kg).All injections were performed intraperitoneally. After administration for 3 consecutive weeks, the animals werekilled and testis tissues were used for assessment of oxidative stress markers including lipid peroxidation(LPO), glutathione (GSH) content and protein carbonyl (PrC), and sperm analysis. Mitochondria were isolatedfrom rat’s testis using differential centrifugation technique and were studied in terms of mitochondrialviability, mitochondrial membrane potential (MMP), and mitochondrial swelling. The other part of the tissuesample was placed in RNA protector solution for assessment of Bax and Bcl-2 gene expression through realtime polymerase chain reaction (real-time PCR) assay.Findings: Tramadol caused a significant decline in epidermal sperm count, motility, and morphology, as wellas a significant decrease in GSH level and mitochondrial function, and a significant evaluation of LPO, PrC,MMP, and mitochondrial swelling. In addition, tramadol induced a significant decrease in Bcl-2 geneexpression, and increase in Bax gene expression. However, pretreatment of rats with MT improved spermanalysis, and testicular antioxidative status, and mitochondrial function. Furthermore, MT pretreatmentregulated testicular Bcl-2 and Bax expressions.Conclusion: Considering the protective effects of MT against reproductive toxicity induced by tramadol, thiscompound can be used as a possible agent for the prevention and treatment of tramadol-induced reproductivetoxicity.